2011
DOI: 10.1353/ces.2011.0048
|View full text |Cite
|
Sign up to set email alerts
|

"We Expect Much of You": Enlisting Youth in the Policing of Marginalized Communities

Abstract: In this paper, we examine a police summer program for youth from marginalized communities designed to both provide valuable experiences and opportunities as well as improve the problematic relationship between marginalized youth and police. Using the concepts of racialization, governance, and interest-convergence, we consider how such institutionally sponsored programs socialize youth into a value system that fosters self-governance and restraint, particularly in the case of youth who, because of where they li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Few studies have explored how Black people in Canada perceive the police. A few have explored youth relations with police (Adorjan et al 2017; Chow 2012), and others have focused on youth encounters with police (Chapman-Nyaho et al 2011;Giwa et al 2014;James 1998). Owusu-Bempah (2014) investigated how Black men experience and perceive the police, and found that Black men reported more frequent and hostile encounters with police than other groups.…”
Section: Experiences Of Policing Among African Canadian Communitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have explored how Black people in Canada perceive the police. A few have explored youth relations with police (Adorjan et al 2017; Chow 2012), and others have focused on youth encounters with police (Chapman-Nyaho et al 2011;Giwa et al 2014;James 1998). Owusu-Bempah (2014) investigated how Black men experience and perceive the police, and found that Black men reported more frequent and hostile encounters with police than other groups.…”
Section: Experiences Of Policing Among African Canadian Communitiesmentioning
confidence: 99%
“…It can be used to explore the close relationships between race, racism, and the state, and "the ongoing challenges posed by racial liberalism, which promises liberty, equity, and social justice but comfortably coexists with deep economic and social inequalities and social exclusion" (Razack et al 2010: 10). It is a race-conscious approach to research, often in relation to education (Huber and Solorzano 2015;Hylton 2012) and the criminal justice system (Chapman-Nyaho et al 2011;Giwa et al 2014;Williams 2013). It challenges the idea of "colourblindness" -the assumption that racism no longer exists, and therefore no decisions in society or by government should are based on race (Aylward 1999;James et al 2010).…”
Section: Critical Race Theorymentioning
confidence: 99%